Longitudinal Effects of Computer-Mediated Communication Anxiety on Interaction in Virtual Teams - Fuller, Robert M.; Vician, Chelley M.; Brown, Susan A. (IEEE transactions on professional communication, 2016)
Research problem: Organizations continue to rely upon virtual teams, yet knowing how, and for how long, individual members' computer-mediated communication (CMC) anxiety affects virtual team interactions and performance outcomes is not well-known. Research questions: (1) What is the relationship between CMC anxiety and virtual team participation? (2) How does this relationship influence the perceptions of individual performance? (3) Does this relationship persist over time? Literature review: A literature review including communication and media structures, input-mediator-output team effectiveness, and individual CMC anxiety elements indicate researchable negative effects upon virtual team interaction and participation in CMC environments. Higher levels of individual CMC anxiety could dampen participation quantity, participation type (task versus social), participation quality, and perceptions of individual performance. Further, the initial negative interactions and behaviors could persist over time. Methodology: This quantitative quasiexperimental study involved surveying, observing, and coding the interactions of 22 virtual project teams (consisting of a total of 110 individuals) over a span of four months. The teams used a CMC tool with shared file space and discussion boards to coordinate database design and implementation work. Data were collected from questionnaire surveys, individual message postings, and team project scores. Individual message postings were coded to measure participation quality (task focus and topic introductions) and participation quantity (message count and words per message). Data were analyzed using repeated-measures multivariate analyses along with follow-up univariate statistical testing. Results and conclusions: The results indicate that individuals with higher levels of CMC anxiety participated less, sent fewer task-oriented messages, introduced fewer novel topics, and were rated more poorly by team members on their performance compared to individuals with lower levels of CMC anxiety. The results also show that CMC-anxious individuals do send relatively more social-oriented messages, perhaps to compensate for typical apprehensive communication behaviors in a virtual team environment. In addition, participation quality and quantity and perceptions of performance by CMC-anxious team members do not significantly improve, even with repeated interactions over CMC. Although study participants evidenced high engagement with the project tasks, the study is limited by its use of student subjects. The study suggests the importance of team leaders and role definitions for virtual teams, to counteract potential unintended effects of CMC technology use masking actual participation and contribution of virtual team members. Future research could investigate the efficacy of interventions for reducing the negative impacts of CMC anxiety in virtual team performance, as well as the influence of individual structures such as CMC anxiety in the use of CMC and team structures in the virtual team environment.